2002
DOI: 10.1620/tjem.197.151
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Systolic and Diastolic Function During Early Neonatal Period Using Transthoracic Echocardiography.

Abstract: To examine the effects of ductal closure on left ventricular (LV) systolic and diastolic function during the early neonatal periods, 45 normal term neonates delivered after uncomplicated pregnancies (mean 39 weeks) were studied using two-dimensional and Doppler echocardiography. We measured ductus arteriosus size, arterial blood pressures, ascending aortic size, LV dimensions, and transmitral flow velocity patterns and calculated LV output and rate-corrected fiber shortening fraction (mVcfc) at 2, 12, 24, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Shiota et al reported that LVDds determined with conventional echocardiography were significantly larger 2 h after birth than 12 h after birth and later [4]. Harada et al [5] and Agata et al [6] reported similar results using the pulsed Doppler technique.…”
Section: Influence Of the Flow Through The Ductus Arteriosusmentioning
confidence: 87%
See 2 more Smart Citations
“…Shiota et al reported that LVDds determined with conventional echocardiography were significantly larger 2 h after birth than 12 h after birth and later [4]. Harada et al [5] and Agata et al [6] reported similar results using the pulsed Doppler technique.…”
Section: Influence Of the Flow Through The Ductus Arteriosusmentioning
confidence: 87%
“…There have been some reports regarding LVDds during early neonatal periods. However, these reports did not discuss the influence of the elliptic shape in the short-axis view [4][5][6]. The purpose of this study was to determine the implications of LVDd data determined during this period.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is well known that the DA constricts rapidly after birth, with functional closure occurring within 12 to 36 h in the majority of term infants. Experimental data for DA diameter (DAD) changes in humans can be found in Rasanen et al (11), for the full-term fetus, and in several other publications (25)(26)(27)(28) for term neonates, during the first 24 h of life. To model DA closure, we used a dynamic resistance that increases with neonatal age.…”
Section: Methodsmentioning
confidence: 99%
“…may influence echocardiographic parameters (1,2). With birth, neonatal circulation is established so that lungs begin to perform gas exchange, pulmonary blood flow is increased and pulmonary vascular resistance is decreased (3).…”
mentioning
confidence: 99%